Frankincense ameliorates endometriosis via inducing apoptosis and reducing adhesion - Min Kyoung Cho; Jung-Sook Jin; Yunju Jo; Jung Ho Han; Su Shin; Sung-Jin Bae; Dongryeol Ryu; Jongkil Joo; Jang-Kyung Park; Ki-Tae Ha (Integrative Medicine Research)
Background: Frankincense, a resin derived from trees of the Boswellia genus, has been used as an incense and a type of herbal medicine for treating inflammatory diseases such arthritis, chronic bowel illness, and asthma. While endometriosis is a well-known inflammatory gynecological illness caused by the ectopic attachment and development of uterine tissue over the menstrual cycle, the impact of frankincense on this illness is poorly understood. The purpose of this study was to explore the effects of frankincense on endometriosis. Methods: We used a network pharmacological assessment, in vitro and in vivo investigations with a human endometriotic cell line as well as a syngeneic uterine transfer mouse model. High-performance liquid chromatographic analysis was used to compare water-extracted frankincense (Fr) to its reference compounds and validate the sample. Results: A network pharmacological analysis suggested a positive effect of Fr on endometriosis. Fr relieved endometriosis by reducing ectopic endometrial adherence and development, according to both in vivo and in vitro models. We suggested that the ER stress/p53-apoptosis and chemokine-migration/adhesion pathways underlie Fr's anti-endometriotic action using RNA sequencing and bioinformatic analysis. Conclusion: This study revealed the potential effect of Fr on endometriosis using an experimental investigation. Fr may have the potential to be an effective and safe treatment for endometriosis.